Land acquisitions and foreign direct investment - challenges and opportunities for developing countries : case study of Kisarawe District, Tanzania; focusing small scale farmers - Hamal, Bishwash (2011)
International investors have recently shown a fast growing interest in large scale acquisitions of farmlands in developing countries. Lands, which only a short time ago seemed outside of interest are now being sought by international investors. Concern of food security, high food and oil prices, and scope of alternative energy to produce agrofuels are seen as primary push factors in this fast-evolving context. Foreign investors are typically large, wealthy transnational firms or rich governments, while host governments are poor, at war, or embroiled in political conflict. More importantly, in between are the poor small scale farmers of third world countries who solely depend on their land for survival. It is a new burning subject hence except media reports there are very limited materials available on this issue. Moreover, the few published literature‘s objective is just to open up the topic and to provide initial mapping of issues, promote debate and pave the way for further research but not to come up with definitive answers.‘ Therefore researches in this field are much sought after. This research was carried out in Kisarawe district; Tanzania where Sun Biofuels, UK based Bifofuel Company acquired 9,000 hectares land for commercial production of jatropha for 99 years in 2006. There were 11 villages in that area. Out of 11 villages one village, Mtamba was taken as sample. ‗Case study‘ approach of qualitative methods has been applied for the research. Primary and secondary data are used for the studies which were collected from October 2009 to February 2010 including three filed visits. 12 people were formally interviewed where as 32 small scale farmers participated in questionnaire in Mtamba village. Interviews and questionnaires are primary data where as literature, media reports and others are considered secondary data. The study finds there is huge potential to have win-win situation for both investors and host nations however there is gap between investors and small scale farmers. Farmers without prior education have little or no understanding of land reform policies and henceforth safeguarding their land is rather complicated. Hence, transparency and democratic process must be key issues in land deals. The reports find that at present there are very less negative impacts on issues such as displacement, compensation, environmental degradation in community while keeping hope for better future. At the same time, very high expectations from local people seem unrealistic in shorter term, while undocumented promises and false hopes by investors in unclear terms and conditions may result in frustration and anger.